2012
DOI: 10.1016/j.cmet.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial SKN-1/Nrf Mediates a Conserved Starvation Response

Abstract: SUMMARY SKN-1/Nrf plays multiple essential roles in development and cellular homeostasis. We demonstrate that SKN-1 executes a specific and appropriate transcriptional response to changes in available nutrients, leading to metabolic adaptation. We isolated gain-of-function (gf) alleles of skn-1, affecting a domain of SKN-1 that binds the transcription factor MXL-3 and the mitochondrial outer membrane protein PGAM-5. These skn-1(gf) mutants perceive a state of starvation even in the presence of plentiful food. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
186
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(205 citation statements)
references
References 51 publications
16
186
1
2
Order By: Relevance
“…We discovered that well-fed skn-1 gain-of-function mutant worms upregulated a large number of FAO genes (Fig. 3a), which is consistent with our previous observation that ad libitum-fed skn-1 gain-offunction animals behave as if they are starved 9 . Intriguingly, some FAO genes were found to be downregulated in skn-1 gain-offunction mutants as compared with wild-type controls (Fig.…”
Section: Skn-1 Protects Against Diet-induced Fat Accumulationsupporting
confidence: 79%
See 2 more Smart Citations
“…We discovered that well-fed skn-1 gain-of-function mutant worms upregulated a large number of FAO genes (Fig. 3a), which is consistent with our previous observation that ad libitum-fed skn-1 gain-offunction animals behave as if they are starved 9 . Intriguingly, some FAO genes were found to be downregulated in skn-1 gain-offunction mutants as compared with wild-type controls (Fig.…”
Section: Skn-1 Protects Against Diet-induced Fat Accumulationsupporting
confidence: 79%
“…A role for the transcription factor SKN-1 has been documented under conditions of oxidative stress 4 and lifespan extension [5][6][7][8] , where nutrient availability is either perceived as reduced or is actually reduced. Furthermore, we recently found that gain-offunction mutations in skn-1 induce a starvation-like state 9 . As such, we proposed that a SKN-1-mediated transcriptional programme could mechanistically link proline and fatty acid metabolism.…”
Section: Skn-1 Mediates Lipid Metabolism Responses In Alh-6 Mutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3A). Mianserin did not further increase the stress resistance in the gain‐of‐function mutant skn‐1(lax188) (Paek et al ., 2012) that is already highly resistant to oxidative stress (Fig. S3B), suggesting SKN‐1 is involved in the protective mechanism.…”
Section: Resultsmentioning
confidence: 98%
“…17 SKN-1 was also found to interact with the outer mitochondrial protein PGAM-5. 18 Calcium signalling modulates mitochondrial biogenesis through the calcium/calmodulin-dependent protein kinase II (CaMKII), p38 mitogen activated protein kinase (MAPK) and PGC-1α. 19,20 Although, no clear PGC-1a homolog is present in the nematode genome, we found that SKN-1 activity is modulated by cytoplasmic calcium levels via the CaMKII homolog, UNC-43, upon mitochondrial dysfunction.…”
mentioning
confidence: 99%